A STUDY OF ALISHER NAVOI'S LYRICS AND FOLKLORE - Ozoda Tojiboyeva (Zeta Repository, 2023)
This article examines the scientific activity of the Navoi scholar Natan Mallaev, who studied nationalism in Alisher Navoi's lyrics. Concepts of folk rituals and customs used in Navoi's ghazals are analyzed. Their study by a scientist is covered.